View of Treasure Island
Description attached: Stage set for Pacific Pageant, Gleaming palaces and towers set off by thousands of trees and shrubs make an incomparable setting for the 1939 Golden Gate International Exposition on Treasure Island in San Francisco Bay. This photograph was taken from neighboring Yerba Buena Island.